Characteristics of Overvoltage Protection with Cascade Application of Surge Protective Devices in Low-Voltage AC Power Circuits - RADULOVIC, V. (Advances in Electrical and Computer Engineering, 2015)
Surge Protective Devices (SPDs) are widely used for protection of the equipment in low-voltage AC power circuits against wide variety of surges. Cascade application of SPDs starting at the service entrance of a building and downstream toward near sensitive equipment is intended to ensure optimal energy distribution among installed SPDs, as well as proper equipment protection against surges. Characteristics of overvoltage protection with two-stage application of SPDs have been analyzed in the paper through performed measurements, followed by simulations and numerical modeling using the ATP/EMTP and MATLAB Simulink. Parametric analysis of the protection's characteristics in wide range of influencing factors has been performed in order to define a set of applicable solutions for proper selection and performance of SPDs.